1991
DOI: 10.1099/00221287-137-3-629
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol catabolism in Aspergillus nidulans

Abstract: Glycerol is catabolized in Aspergillus nidulans by glycerol kinase and a mitochondrial FAD-dependent sn-glycerol-3-phosphate dehydrogenase. The levels of both enzymes are controlled by carbon catabolite repression and by specific induction. Biochemical and genetical analyses show that dihydroxyacetone and D-glyceraldehyde are converted into glycerol and then catabolized by the same pathway. D-Glyceraldehyde can be reduced by NADP+-dependent glycerol dehydrogenase or by alcohol dehydrogenase I, while dihydroxya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 28 publications
1
50
0
3
Order By: Relevance
“…Many microorganisms can use glycerol as a carbon source (9,10,11). The bacterial glycerol metabolic pathway is known as a dehydrogenation pathway and a phosphorylation pathway (9).…”
mentioning
confidence: 99%
“…Many microorganisms can use glycerol as a carbon source (9,10,11). The bacterial glycerol metabolic pathway is known as a dehydrogenation pathway and a phosphorylation pathway (9).…”
mentioning
confidence: 99%
“…Many microorganisms, including lactic acid bacteria, utilize glycerol in a phosphorylation pathway rather than in a dehydrogenation pathway (4,5,6,24,25,26). In contrast, W11 utilized glycerol efficiently in only the dehydrogenation pathway (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The missing link in this pathway is an L-threo-3-deoxy-hexulosonate aldolase that would convert L-threo-3-deoxy-hexulosonate to pyruvate and L-glyceraldehyde. It was earlier suggested that D-galacturonate is metabolized through a non-phosphorylating pathway in the mold Aspergillus nidulans (9,10). However it was speculated that D-glyceraldehyde is an intermediate (11).…”
mentioning
confidence: 99%